Effects of small-volume soccer and vibration training on body composition, aerobic fitness, and muscular PCr kinetics for inactive women aged 20-45 - Luke J. Connolly; Suzanne Scott; Magni Mohr; Giorgos Ermidis; Ross Julian; Jens Bangsbo; Sarah R. Jackman; Joanna L. Bowtell; Rosemary C. Davies; Susan J. Hopkins; Richard Seymour; Karen M. Knapp; et al. (Elsevier, 2014)
Purpose: The present study investigated the effects of 16 weeks of small-volume, small-sided soccer training soccer group (SG, n = 13) and oscillating whole-body vibration training vibration group (VG, n = 17) on body composition, aerobic fitness, and muscle PCr kinetics in healthy inactive premenopausal women in comparison with an inactive control group (CO, n = 14). Methods: Training for SG and VG consisted of twice-weekly 15-min sessions with average heart rates (HRs) of ∼155 and 90 bpm respectively. Pre- and post-measurements of body composition (DXA), phosphocreatine (PCr) on- and off-kinetics, and HR measurements during standardised submaximal exercise were performed. Results: After 16 weeks of training in SG, fat percentage was lowered (p = 0.03) by 1.7% ± 2.4% from 37.5% ± 6.9% to 35.8% ± 6.2% and the PCr decrease in the quadriceps during knee-extension ramp exercise was attenuated (4% ± 8%, p = 0.04), with no changes in VG or CO (time-group effect: p = 0.03 and p = 0.03). Submaximal exercise HR was also reduced in SG after 16 weeks of training (6% ± 5% of HRmax, p = 0.01). Conclusion: Short duration soccer training for 16 weeks appears to be sufficient to induce favourable changes in body composition and indicators of aerobic fitness and muscle oxidative capacity in untrained premenopausal women.